Prosedur, Tantangan, dan Solusi dalam Penerapan Real Time Gross Settlement pada Bank Sumsel Babel Cabang Jakabaring - Ahmad Rizky Amaldi; Fitriasuri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the procedures, challenges, and solutions in the implementation of the Real Time Gross Settlement (RTGS) system at Bank Sumsel Babel Jakabaring Branch. The research is motivated by the importance of fast, secure, and efficient payment systems in supporting banking operations, particularly in large-value interbank transactions. The research method employs a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Primary data sources were obtained directly from Bank Sumsel Babel Jakabaring Branch employees, including Tellers and the Administration, General, & Accounting Unit (UAUK), as well as RTGS service users. The results show that the RTGS implementation procedures at Bank Sumsel Babel Jakabaring Branch are generally in accordance with Bank Indonesia regulations, although there is an adjustment in service hours ending at 3:00 PM compared to BI's regulation until 4:45 PM. The main challenges faced are operational risks due to human error, such as incomplete form filling by customers, incorrect account number and recipient name entries, and difficulties in identifying less familiar destination banks. The solutions implemented include improved administrative accuracy by officers, more assertive customer education, data re-verification, and priority reprocessing of transactions in the event of returns. This study concludes that RTGS implementation at Bank Sumsel Babel Jakabaring Branch has been effective, supported by a two-way commitment between the bank and customer discipline.